Hemp in History: An Evolutionary Perspective on its Types and Uses - Imran, Ali; Ahmad, Muhammad; Ali, Awais; Azhar, Muhammad; Syed, Quratulain; Abidi, Hussain Imam; Hussain, Sajid (Indus Journal of Bioscience Research, 2025)
Hemp (Cannabis sativa L.) has played an integral role to human civilization from an ancient crop used for fiber and food into modern plant with diverse applications in industries ranging from textile to medicines. As one of the earliest domesticated crops, its uses have varied from textile production to medicinal applications, and in modern times, its revival has generated renewed interest for industrial, environmental, and therapeutic purposes. This review explores the historical trajectory of hemp, its geographic spread, key historical periods, industrial uses, challenges, and its present-day resurgence.